2015
DOI: 10.1002/2014jb011689
|View full text |Cite
|
Sign up to set email alerts
|

The strength anisotropy of localized compaction: A model for the role of the nature and orientation of cross‐beds on the orientation and distribution of compaction bands in 3‐D

Abstract: The field observations indicate that the low-angle bed-parallel compaction bands and the high-angle-to-bedding compaction bands occur only in cross-beds with certain range of bedding orientations in the Aztec Sandstone at the Valley of Fire State Park (NV). The hypothesis is that the primary underlying mechanical reason for this phenomenon is the strength anisotropy of localized compaction in anisotropic sandstones. In this paper, we used a quadratic failure criterion to describe the strength anisotropy of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 74 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Deng and Aydin [2012] investigated the influences of cross-beds on the distribution of compaction bands in this sandstone. The primary mechanical reason for their distribution is thought to be the strength anisotropy of localized compaction [Deng and Aydin, 2015] induced by the cross-bedding [Deng et al, 2015b].…”
Section: Introductionmentioning
confidence: 99%
“…Deng and Aydin [2012] investigated the influences of cross-beds on the distribution of compaction bands in this sandstone. The primary mechanical reason for their distribution is thought to be the strength anisotropy of localized compaction [Deng and Aydin, 2015] induced by the cross-bedding [Deng et al, 2015b].…”
Section: Introductionmentioning
confidence: 99%
“…These authors demonstrated that the compaction band domains (assemblages of compaction bands of different orientations) are mostly confined within the depositional domains (dune units characterized by certain cross-beds orientation therein). This phenomenon could be related to the strength anisotropy of localized compaction (Deng and Aydin, 2015) induced by the cross-bedding related anisotropy, which was measured to be about 13% (Deng et al, 2015a). Because…”
mentioning
confidence: 96%